2019
DOI: 10.3390/pharmaceutics11020068
|View full text |Cite
|
Sign up to set email alerts
|

Amorphisation of Free Acid Ibuprofen and Other Profens in Mixtures with Nanocellulose: Dry Powder Formulation Strategy for Enhanced Solubility

Abstract: The formulation of arylpropionic acid derivatives (profens), which are poorly soluble Biopharmaceutical Classification System (BCS) Type II drugs, has a strong impact on their therapeutic action. This article shows that heat-treated powder mixtures of free acid profens with high surface area Cladophora cellulose induces drug amorphization and results in enhanced solubility and bioavailability. Similar mixtures produced using conventional low surface area cellulose, i.e., microcrystalline cellulose, does not pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…We have recently shown that the formulation of ibuprofen and other arylpropionic acid derivatives with nanocellulose can result in enhanced solubility and rapid dissolution rate due to amorphization of the drug [30]. Ordinary MCC, which has a low surface area, fails to produce this effect.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that the formulation of ibuprofen and other arylpropionic acid derivatives with nanocellulose can result in enhanced solubility and rapid dissolution rate due to amorphization of the drug [30]. Ordinary MCC, which has a low surface area, fails to produce this effect.…”
Section: Introductionmentioning
confidence: 99%
“…The cellulose batches used in this study were identical to those used previously [12,13]. Notably, the pore volume of CLAD was 276 times and the specific surface area of CLAD was about 108 times larger than that for MCC as derived from N 2 gas sorption analysis.…”
Section: Resultsmentioning
confidence: 92%
“…We have previously shown that heat-assisted mixing of poorly soluble drugs from varying pharmacological classes with high surface area nanocellulose results in enhanced solubility and dissolution rate in biorelevant media. In particular, the latter effect was shown for NSAIDs from arylpropionic acid derivatives, e.g., ibuprofen, flurbiprofen, ketoprofen, and naproxen [12], as well as dihydropyridine-type calcium channel blockers, e.g., nifedipine, felodipine [13]. In this article, we extend this strategy and demonstrate improved formulation for a model problem drug featuring both poor solubility and unusually high number of polymorphs.…”
Section: Introductionmentioning
confidence: 84%
“…This results in a loss of dissolution and solubility advantage of the amorphous state. Mainly, an amorphous dosage form of ibuprofen sodium was proved to have long-term stability issue and alteration of dissolution profile as determined by Mantas et al ( 58 ).…”
Section: Discussionmentioning
confidence: 99%